2010
DOI: 10.3189/002214310792447806
|View full text |Cite
|
Sign up to set email alerts
|

Snow grain-size profiles deduced from microwave snow emissivities in Antarctica

Abstract: International audienceSpaceborne microwave radiometers are an attractive tool for observing Antarctic climate because their measurements are related to the snow temperature. However, the conversion from microwave emission to snow temperature is not simple and strongly depends on the emissivity through snow properties. This difficulty in predicting the snow property profile for Antarctic conditions is the main bottleneck in the retrieval of accurate climate information from microwave radiometers. We attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 101 publications
(140 reference statements)
1
43
0
1
Order By: Relevance
“…The rms errors reported in Table 2 show that the agreement is, in general, better by a factor of 2 for SP1 than SP2, and better by a factor of around 5 for the vertical than the horizontal polarization. However, the error is relatively independent of the frequency, which indicates that the vertical gradient of snow grain size and density is well captured by the measurements (Brucker et al, 2010).…”
Section: Relationship Between Brightness Temperature and Snow Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…The rms errors reported in Table 2 show that the agreement is, in general, better by a factor of 2 for SP1 than SP2, and better by a factor of around 5 for the vertical than the horizontal polarization. However, the error is relatively independent of the frequency, which indicates that the vertical gradient of snow grain size and density is well captured by the measurements (Brucker et al, 2010).…”
Section: Relationship Between Brightness Temperature and Snow Propertiesmentioning
confidence: 91%
“…They have several advantages over other remote sensing techniques: high sensitivity to snow properties (temperature, grain size, density), subdaily coverage in the polar regions, and independence of cloud conditions and solar illumination. Typical applications for ice sheets aim to retrieve snow temperature (Shuman et al, 1995;Schneider and Steig, 2002;Schneider et al, 2004), snowmelt (e.g., Zwally, 1977;Abdalati and Steffen, 1995;Torinesi et al, 2003), snow accumulation (Vaughan et al, 1999;Arthern et al, 2006), grain size (Brucker et al, 2010;Picard et al, 2012), thermal properties (Koenig et al, 2007;Picard et al, 2009) or surface state (Shuman et al, 1993;Champollion et al, 2013). Passive microwave data are also widely used in assimilation schemes to constrain atmospheric analyses for which the surface emissivity is an issue, particularly over Antarctica (Guedj et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For this, for each 10-day period from 1999 to present, the SSA in both layers is optimized so that the model predictions at 150 and 89 GHz match the satellite observations. To relate the SSA to the grain size metric r required by the DMRT theory, an empirical scaling coefficient is used according to Brucker et al (2010), such that SSA = 3/(ρ ice r 2.8 ). This method is simple because using two observations it considers only two unknowns, while the density and layer thickness are probably variable and are known to affect microwave signal as well (even if this effect is of second order compared to the SSA).…”
Section: Satellite Observationsmentioning
confidence: 99%
“…8c. For instance, Brucker et al (2010) have found the highest grain size vertical gradient in the regions of the WP zone.…”
Section: Discussionmentioning
confidence: 98%